Unmasking Motherhood: Journeys of Self-Discovery in Mary Melfi’s Italy Revisited: Conversations with My Mother and Genni Gunn’s Tracing Iris - Rorato, Laura (Italian Canadiana, 2020)
This paper will explore how the quest for the mother (whether the missing one of Gunn’s novel or the living one of Melfi’s memoir) leads the protagonists of both books to rediscover their mother tongue, that is a language based on communication and community building (Parmod, 2008), or as Kate defines it in Tracing Iris, a body language. It is through this language that both characters are able to challenge the patriarchal concept of motherhood and, in particular, the stereotype of the good versus the bad mother. The quest for the mother in both texts can be defined as a journey through the protagonists’ past that leads them also to problematize the notion of motherland. Significantly, both texts emphasize the idea of resurrection (the resurrection of the self) and their structures seem to mirror the trajectory identified by Podnieks and O’Reilly (2010) as representing the transition from daughter-centric to matrifocal narratives. Such narratives are effective tools in unmasking motherhood not only because they enable mothers to have a voice but also because they represent a different kind of mothering, the mothering of writing (Nayar 2008, p. 140). According to Nayar, textual mothering, by giving birth to stories and narratives, allows motherhood to be reinterpreted as a situation of power and identity (Nayar 2008, p. 140).